EFFECTS OF QUALITY OF LIFE IMPROVEMENT PROGRAM AMONG VILLAGE HEALTH VOLUNTEERS, PHU SANG SUB-DISTRICT, PHU SANG DISTRICT, PHAYAO PROVINCE - สมนาม , สงกรานต์; ปัญญาใสโสภณ, ธณกร; ธำรงศ์วรกุล , พีสสลัลฌ์ (Primary Health Care Journal (Northeastern Edition), 2024)
This quasi-experimental study aimed to compare the quality of life of village health volunteers before and after participating in a quality of life development program and between the experimental and control groups. The study involved 199 village health volunteers, with 30 in the experimental group and 30 in the control group, selected through purposive sampling. Data were collected using a quality of life assessment questionnaire. The experimental tool was a quality of life development program, which included activities such as knowledge sharing, group counseling, relationship-building skills training, a local nutrition guide, yoga and Tai Chi exercises, social communication, social adaptation, and follow-up and reminders via the Line application. Data were analyzed using frequency, percentage, mean, and standard deviation. The comparison of mean scores was conducted using the Dependent sample t-test and Independent sample t-test. The findings showed that: I. After the intervention, the experimental group had significantly higher average quality of life scores compared to before the intervention at the 0.05 significance level. II. The experimental group also had significantly higher quality of life scores compared to the control group at the 0.05 significance level. In summary, developing the quality of life for village health volunteers should focus on providing useful skills and experiences through a combination of guidance and activities such as relationship-building, social communication, social adaptation, and regular follow-up and reminders through the Line application.